Integration of Triple Bottom Line (People, Planet, Profit) in Sustainability Accounting and Reporting in Manufacturing Companies - Hamada, Maurheen Queena; Kurnia, Silvi Kurnia; Fadhulloh, Achmad Alfin Nahdi; Nugraha, Viery Erlangga; Pandin, Maria Yovita R (Lead Journal of Economy and Administration, 2025)
This study aims to evaluate the integration of the Triple Bottom Line (TBL) approach People, Planet, and Profit into Sustainability Accounting and Reporting (SAR) practices within manufacturing companies in Indonesia. The analysis focuses on four major corporations: PT Unilever Indonesia Tbk, PT Semen Indonesia Tbk, PT Indofood Sukses Makmur Tbk, and PT Astra International Tbk, all of which have consistently published sustainability reports during the 2021–2024 period. A qualitative descriptive method was applied, using content analysis of sustainability reports based on the Global Reporting Initiative (GRI) Standards and the Indonesian Financial Services Authority Regulation No. 51/POJK.03/2017. The findings reveal that the profit (economic) aspect is more prominently and consistently reported, while the people (social) and planet (environmental) aspects tend to be symbolic and lack in-depth, measurable indicators. Although all companies demonstrate a commitment to sustainability, there are noticeable differences in the depth of disclosure and the selection of non-financial indicators. These results highlight the need for harmonized reporting standards, enhanced internal capacity, and more relevant qualitative metrics. Integrating TBL principles into SAR provides a more accountable and comprehensive reporting framework, supporting both internal strategic decision-making and external transparency to stakeholders. This study contributes to the advancement of more substantial and coordinated sustainability reporting practices in Indonesia’s manufacturing sector.